Pengembangan Kemampuan Kreativitas dalam Pembelajaran IPS - Fadillah, Allya; Amini, Amini; Sahfitri, Anggi Ayu; Lubis, Kamalia; Mahyuni, Lela; Abdi, Khoirul (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The field application shows that social science education is still mainly theoretical. The attitude that social science education is only "for memorization" is only partially responded to by teachers who solely focus on delivering theoretical content. The classroom learning process shows that schools have not been able to optimize students' creative thinking abilities, especially in using those abilities to solve everyday challenges. To encourage student creativity, teachers must have their own creative skills. If teachers act as creative pilots for the class, student creativity will also emerge. To achieve the true goals of social science education, the lesson materials outlined in the syllabus must be well developed. New ideas or ideas that have never been thought of before are considered creative. In the field of education, creativity is very important for understanding lessons or understanding all future tasks. Therefore, efforts to foster creativity should begin from elementary school or early childhood. Creative expression and the actualization of personal identity in relation to oneself, nature, and others is an experience.